ECONOMIC GROWTH, REGIONAL SIZE, AND LOCAL REVENUE: ANALYZING THEIR IMPACT ON FINANCIAL PERFORMANCE OF LOCAL GOVERNMENTS IN INDONESIA - Adi Wijaya; Khairudin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The performance of the government is the understanding of the regions in finding and managing regional finances that are useful for the needs and support of the continuation of the government system. Financial performance continues to increase can provide good to the welfare of the community, the more resources that can be used in maximizing services to the community and can also finance regional development and government implementation, the more independent a region is in creating its regional potential. The problem of financial performance in general, the performance of the independence of the Regency/City Government in Lampung is still relatively low. One of the problems with the financial performance of the Lampung Provincial government in 2023 is related to cash management. The purpose of this research is to provide a more in-depth knowledge literacy about what factors have an impact on the financial performance of local governments, as well as provide appropriate recommendations to a local government to improve the financial performance of its government in the future. This study involved 14 district governments and 2 cities in Lampung Province as a sample determined based on purposive sampling with the criteria of the regency/city government that has data on the financial independence ratio that is categorized as lacking. The analysis used was in the form of multiple linear regression and hypothesis test (t-test).